A atuação Política da Coordenação de Proteção dos Direitos dos Povos Indígenas e das Populações Tradicionais (CPPITA) na Secretaria de Justiça e Direitos Humanos (SEJUDH) - GOMES, Izaquiel Mateus Macedo (Universidade Federal do Pará, 2015)
Institutions that deal with indigenous issues are present in the political scene, mainly from the Indian Protection Service (SPI), a posteriori, the National Indian Foundation (FUNAI) these national imprint. The indigenous issue in the state of Pará gain some visibility in the municipal government with the mayor of Bethlehem Edmilson Rodrigues (1997-2000, 2001-2004) and then with the Governor Ana Julia Carepa (2007-2010). Given the reforms the state executive, the Department of Justice becomes Secretary of Justice and Human Rights, which congregate demands of various political minorities between her coordination that deals with the protection and the rights of indigenous and traditional populations in which an indigenous came forward during the rule Ana Julia. Although space favored by the government Ana Julia was not possible to effect a state Indian policy seeking to understand the topic in local terms, there will be a historical review of the relationship between state and Indians in order to provide a framework DAS questions that have guided the dialogue in institutional aspect. THEN The analysis of political action Coordination of Protection of the Rights of Indigenous Peoples and Traditional Populations (CPPITA) intra-inter Secretariat of Justice and Human Rights (SEJUDH) given the new political scenario which is configured with the Brazilian redemocracia.